Analisis Aktivitas Belajar Siswa Kelas X pada Mata Pelajaran Biologi di SMA Negeri 10 Palembang - Sulton Nawawi; Aseptianova; Gevina Intan Anggreiny (Mangifera Edu, 2020)
Learning activities are activities carried out to produce changes in knowledge and skills in students. Learning activities contribute to the learning outcomes that students will get. The purpose of this study was to determine student learning activities in class X virus material at SMA Negeri 10 Palembang. This research is a type of quantitative description research. The study population was all Grade X MIA students of SMA 10 Palembang. Class X MIA 2, MIA 4, MIA 5, and MIA 7 research samples were taken using a purposive sampling technique. Data obtained using observation sheets. The results of class X MIA 2 obtained a percentage of 67% including the excellent category, class X MIA 4 gained a percentage of 67% including the excellent category, class X MIA 5 gained a percentage of 65% including the excellent category and class X MIA 7 with a percentage of 62% including the excellent category. Student learning activities are categorized as useful because students follow learning by carrying out various learning activities. The conclusion is that the average learning activity of class X students of SMA Negeri 10 Palembang on virus material obtains 65%, including the excellent category. The highest percentage is emotional activity and mental activity, with a percentage of 71%. The activity that gets the lowest percentage is drawing activity with a percentage of 48%.